Five challenges of the rights discourse - Asís, Rafael de (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2024)
This work presents five great challenges of the theory of rights: the power of rights, the satisfaction of evident rights, the regulation of disruptive technologies, vulnerability and discrimination, and training and awareness.
Keywords: human rights; vulnerability; discrimination